Effects of genetic mutations on left ventricular myocardial mechanics and fibrosis patterns in hypertrophic cardiomyopathy - Minjeong Kim; Yoonjung Kim; Hyemoon Chung; Jiwon Seo; Chul Hwan Park; Tae Hoon Kim; Se-Joong Rim; Kyung-A Lee; Eui-Young Choi (Scientific Reports)
Abstract Myocyte disarray and fibrosis are underlying pathologies of hypertrophic cardiomyopathy (HCM) caused by genetic mutations. However, the extent of their contributions has not been extensively evaluated. In this study, we investigated the effects of genetic mutations on myofiber function and fibrosis patterns in HCM. A total of 133 patients with HCM underwent chamber geometry, late gadolinium enhancement (LGE), and T1-mapping evaluation using 1.5T cardiac magnetic resonance (CMR) imaging, echo-derived diastolic function analyses, and genetic testing. Left ventricular (LV) segmental and global longitudinal strain (LS), circumferential strain (CS), and rotation were measured using feature tracking analysis. Patients with sarcomere-associated mutation (SM, n = 41) exhibited lower LV-CS (all three slices) and higher basal rotationendo, along with a higher prevalence of midepicardial LGE. The relationship between SM and LV-CSmyo was independent of LGE amount (ß = 0.239, p = 0.008). However, global LS and E/e’ were not correlated with SM but were associated with LV mass index and LGE extent. SM was significantly correlated with the presence of midepicardial LGE (odds ratio 5.81, 95% confidence interval 2.15–15.72, p = 0.001), independent of LV mass index, hypertrophy pattern and E/e’. Augmented LV basal segmental rotation was significantly associated with dynamic obstruction. Circumferential fiber dysfunction and midepicardial fibrosis were related to SM, independent of the extent of LV hypertrophy. However, longitudinal fiber function was correlated to the extent of hypertrophy and fibrosis, regardless of SM. Subendocardial fibrosis did not show a significant association with SM.